Effect of productive zakat program on the improvement of welfare in Sragen regency - Abdul Haris Romdhoni (Jurnal Ekonomi & Keuangan Islam, 2018)
This study aims to determine: 1) the effect of capital on improving the welfare of poor communities in Sragen Regency; 2) the influence of income on improving the welfare of the poor in Sragen Regency; 3) the impact of consumption on the improvement of the welfare of the poor in Sragen Regency; on improving the welfare of the poor in Sragen Regency; and 4) the influence of capital, income and consumption together on improving the welfare of poor communities in Sragen Regency.The research method used in this research is quantitative research method. This research was conducted in LAZISMU Sragen regency. The population in this research is all the students in LAZISMU Sragen regency. Sampling technique in this research use accidental sampling with sample as much as 90 mustahiq. Test the instrument using validity and reliability test. Methods of data analysis using multiple linear regression analysis, classical assumption test consisting of normality test, multicollinearity test, heteroskedastic test, F test, and t test.The results of this study indicate that: 1) capital affects the improvement of welfare. It is obtained from tcount (9,113)> ttable (1,992) and probability 0.000 <0,05; 2) income affects the improvement of welfare. It is obtained from tcount (2,760)> ttable (1,992) and probability of 0,007 <0,05; 3) consumption affects the improvement of welfare. It is obtained from the tcount (2,241)> ttable (1,992) and the probability of 0,028 <0,05. 6) capital, income and consumption affect the improvement of welfare. It is obtained from the value of Fcount of 162.645> Ftable = 2.37 and sig. 0,000 <0,05. Multiple linear regression equation in this research that is: Y = 3,299 + 0,703X1 + 0,208X2 + 0,090 X3.